Co-regulatory activity of hnRNP K and NS1-BP in influenza and human mRNA splicing - Matthew G. Thompson (Nature Portfolio, 2018)
Alternative splicing of influenza A virus (IAV) M transcript is regulated by hnRNP K and NS1-BP, but mechanistic details are unknown. Here, Thompson et al. show how hnRNP K and NS1-BP bind M mRNA and that these proteins regulate splicing of host transcripts in both the absence and presence of IAV infection.